Estimating age‐at‐death in burnt adult human remains using the Falys–Prangle method. Issue 1 (31st December 2020) - Veselka, Barbara; Hlad, Marta; Wolfe Steadman, Dawnie; Annaert, Henrica; Boudin, Mathieu; Capuzzo, Giacomo; Dalle, Sarah; Kontopoulos, Ioannis; De Mulder, Guy; Sabaux, Charlotte; Salesse, Kevin; Sengeløv, Amanda; et al.
Abstract: Objectives: The Falys–Prangle‐method assesses age‐related morphological changes to the sternal clavicle end (SCE), enabling the observation of mature adults from the 5th decade onwards in unburnt human skeletal remains. The aim of this study is to investigate the applicability of the Falys–Prangle‐method on burnt human remains. Materials and methods: Fifty‐two SCE of 40 cremated individuals (out of 86) from the William M. Bass collection of the Forensic Anthropology Center (Knoxville, Tennessee) of known age‐at‐death and sex are available for assessment. Surface topography, porosity, and osteophyte formation are evaluated, after which the calculated composite score is associated with the corresponding age range as described by Falys and Prangle. The method is also applied on an archaeological case study from Oudenburg, Belgium, dating to the Roman period. Results: The assessed age ranges strongly agree with the true age ranges (α = 0.828), suggesting the Falys–Prangle‐method to be applicable on burnt human remains. The case study from Oudenburg yields markedly improved age‐at‐death estimates, significantly enhancing our understanding of the age distribution within this community. Discussion: Information on age‐at‐death is key in the construction of biological profiles of past individuals. The mature adult is often invisible in the archaeological record since most macroscopic age estimation methods do not distinguish beyond 46+ years old. Our study stresses the usefulness of a large‐scale application of the Falys–Prangle‐method, which will increase the visibility of mature adults, especially in archaeological burnt human skeletal collections, where such information is, at present, extremely difficult to obtain.